OPEN: An open-source platform for developing smart local energy system applications. (1st October 2020) - Morstyn, Thomas; Collett, Katherine A.; Vijay, Avinash; Deakin, Matthew; Wheeler, Scot; Bhagavathy, Sivapriya M.; Fele, Filiberto; McCulloch, Malcolm D.
Highlights: Presents the Open Platform for Energy Networks (OPEN), github.com/EPGOxford/OPEN. Integrated modelling, control & simulation framework for smart local energy systems. The object-oriented approach offers modularity, code reuse & extensibility. Development has been motivated by four industry–academic demonstration projects. Case studies demonstrate how OPEN can be extended for new applications. Abstract: This paper presents OPEN, an open-source software platform for integrated modelling, control and simulation of smart local energy systems. Electric power systems are undergoing a fundamental transition towards a significant proportion of generation and flexibility being provided by distributed energy resources. The concept of 'smart local energy systems' brings together related strategies for localised management of distributed energy resources, including active distribution networks, microgrids, energy communities, multi-energy hubs, peer-to-peer trading platforms and virtual power plants. OPEN provides an extensible platform for developing and testing new smart local energy system management applications, helping to bridge the gap between academic research and industry translation. OPEN combines features for managing smart local energy systems which are not provided together by existing energy management tools, including multi-phase distribution network power flow, energy market modelling, nonlinear energy storage modelling and receding horizon optimisation. The platform is implemented in Python with an object-oriented structure, providing modularity and allowing it to be easily integrated with third-party packages. Case studies are presented, demonstrating how OPEN can be used for a range of smart local energy system applications due to its support of multiple model fidelities for simulation and control.